Effectiveness and context dependency of social norm interventions: five field experiments on nudging pro-environmental and pro-social behavior - Mundt, Daria; Batzke, Marlene C. L.; Bläsing, Thanee M.; Gomera Deaño, Sandro; Helfers, Anna (Frontiers in Psychology, 2024)
Social norm interventions hold the potential to change people's behavior. Five field experiments (N = 1163) examined the effects of a simple and easily realizable social norm nudge based on the social media format "Be like Bill". The nudge consisted of a stick figure named Toni that communicated descriptive and injunctive norms regarding pro-environmental or pro-social behaviors. Nudge conditions were compared to no-intervention control conditions. Experiment 1 (N = 179) focused on paper towel consumption in a women's restroom at a German university. The nudge condition used less paper towels than the control condition, d = 0.48. Experiment 2 (N = 183) replicated this result (d = 0.32) in a more diverse setting of a women's restroom at a German Christmas market. Experiment 3 (N = 250) examined differences in the effects of prescriptive (i.e., 'do-norm') versus proscriptive (i.e., 'don't-norm') social norms on paper towel consumption again in a university women's restroom. The effectiveness of both social norm nudge conditions was shown in comparison to the control condition (d = 0.46; d = .40), while the prescriptive and proscriptive social norm manipulations did not differ. Experiment 4 (N = 206) applied the nudging approach to the use of plastic lids in a coffee shop, where no effect was found. Finally, Experiment 5 (N = 345) focused on the pro-social behavior of mask wearing in a bakery towards the end of the Covid-19 pandemic restrictions in Germany. In the nudge condition, more visitors put on face masks compared to the control group, d = .39. Limitations and contextual factors regarding the applicability of our social norm nudge are discussed.